(1) Solution:- (3abx 43a)
= 12a4 b
(2) Solution:- (5xyx 6az)
= 30axyz.
(3) Solution:- (5ax 2X 3ax2 y)
= 15a3 x7 y
(4) Solution:- 8a2 b X (-2b2)
= -16a2 b3
(5) Solution:- (-2abx2) x (10bx3 y z)
= -20ab4 x3 y z
(6) Solution:- (-3p2 q3)x (-6p5 q4 )
= 18 p7q7
(7) Solution:- (-12m2 a2 x 2) x (-2ma2 x2)
= 24 m3 a4 x5
(8) Solution:- (7a3 bx5 y2) x (-3x5 y5 a2 b2 )
= – 21a5 b3 x10y5
(9) Solution:- (2x+3y) (5xy)
= (10x2 y +15xy2)
(10) Solution:- (5x- 4xy) (9x y)
= 45x y – 36 x y
(11) Solution:- (2a2 – 3b2+c2) (a3 b2)
= 2a5 b2 – 3a3 b4+ a3 b2 c2
(12) Solution:- (x3 – y2 + 3xyz) (x4 y)
= x7 y- x4 y3 + 3x5 y z
(13) Solution:- (2a-3b) (3a+2b)
= 6a2 + 4ab- 9ab- 6b2
= 6a2 – 5ab- 6b2
(14) Solution:- (a+ b) (a-b)
= a2 –b2
(15) solution:- (x2+1) (x2-1)
= (x2)2 – (11)2
= (x4-1)
(16) Solution:- (a+ b) (a+ b)
= a3+ a2 b+ ab2 +b3
(17) Solution:- (a2 –a b +b2) (a +b)
= a3+ a2 b – a2 b – a b2+ a b2+ b3
= a3+b3
(18) Solution:- (x+2xy+y) 9x+y)
= x3+yx2+2x2 y+2x2 y+ xy2 +y3
= x3+ 3x2 y+ 3xy2+ y3
(19) Solution:- (x2-2xy+y2) (x-y)
= x2-x2 y – 2x2 y+2x y2+xy2-y3
= x3– 3xy2+ 3xy2– y3
(20) Solution:- (x+2x-3) (x+3)
= x3 + 3x2 + 2x2 +6x- 3x-9
= x3 + 5x2+ 3x-9
(21) Solution:- (a2+ab+ b2) (b2– ab+ a2)
= a2 b2 –a3b+a4 +ab3– a2 b2 +a3b+ b4-ab3+a2 b2
= a4+b4+a2 b2
(22) Solution:- (a+ b +c) (a+ b +c)
= (a + b + c)2
= a2+b2+c2+2ab+2bc+2ca
(23) Solution:- (x2-x3y +x2 y2+ x3y- x2 y2 + xy3+ x2 y2 – xy3+y4)
= x4+ x2 y2 +y4
(24) Solution:- (y2-y+1) (1+y+y2)
= (y2+ y3+ y4-y- y2- y3+1+y+ y2)
= y4+ y2+1
(25) Solution:-
A= x2+xy+y2
B= x-y
Therefore, L.H.S, AB
= (x2+xy+y2) (x-y)
= x3 – y3
= R.H.S
L.H.S=R.H.SS (proved).
(26) Solution:- AB.
= (a2-ab+b2) (a+ b)
= a3+b3
(27) Solution:- L.H.S,
(a2+1) (a – 1) (a2+1)
= (a2-1) (a2+1)
= (a2)2 – (1)2
= a4 – 1
= R.H.S
(28) Solution:- L.H.S,
(x +y) (x-y) (x +y)
= (x2-y2) (x2+y2)
= (x2)2 – (y2)2
= x4-y4
= R.H.S
No comments:
Post a Comment